Qur'an Recitation at Acehnese Gravesites: Practices, Perspectives, and Shifting Factors - Anwar Anwar; Ruhamah Ruhamah; Abdul Manan; Saprijal Saprijal; Faez Syahroni; Zulfa Tuffahati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The Acehnese people have been carrying out the religious practice of reciting the Qur’an at the gravesites for generations. This research aims at determining the practice of reciting the Qur’an at the gravesites, current practices, perspectives, shifting factors, and opinions of Islamic school’s scholars. This research employed observation, interviews, and documentation as its instruments. The gained data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the practice of reciting the Qur’an at gravesites is a ritual carried out by some people at the gravesites individually and in groups. People carry out the current practice of reciting the Qur’an at gravesites starting from three days, seven days, and ten days and nights. They also pay wages to members who recite the Qur’an at the gravesites. Additionally, women continue reciting the Qur’an during Friday prayers to ensure uninterrupted reciting. The perspectives of ordinary people are that reciting the Qur’an at the gravesites symbolizes a form of affection for the deceased's family. Meanwhile, academicians argue that reciting the Qur’an at gravesites is a social phenomenon to continue pre-existing traditions and to maintain sacred values in every religious ritual. Modernists argue that reciting the Qur’an at the gravesites does not need to be a tradition because apart from having no strong basis, the sins of someone who has died are not borne by other people. Meanwhile, scholars argue that reciting the Qur’an at gravesites is recommended in Islamic teachings to pray for the deceased, even if other people recite it. The shifting factors happened because the influence of local culture and foreign culture that people follow the developments of times besides increasing income for people who are invited to recite the Qur’an. Meanwhile, the Imāms of the school of thought argue according to the postulates that reciting the Qur’an at a gravesites is makruh and something that is sunnah, however, if it is done intending to send prayers to the deceased, it is then recommended because it can ease the torment in the graves and get rewards for both those who recite and those who listen to the reciting of the Qur’anic verses.